2022
DOI: 10.1155/2022/4222205
|View full text |Cite
|
Sign up to set email alerts
|

Combustion Characteristics of Briquette Fuel Produced from Biomass Residues and Binding Materials

Abstract: Proper management and effective conversion of biomass residues for biofuel production are crucial to reduce deforestation due to the cutting of trees for cooking and heating as a primary source of fuel and improving energy utilization of households. Thus, this study is aimed at investigating the effects of biomass residues of the coffee husk (CH), sawdust (SD), khat waste (KW), and dry grass (DG) and binding materials prepared from the waste paper pulp (PP) and clay soil (CS) under a low-pressure piston press … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(13 citation statements)
references
References 29 publications
0
8
0
Order By: Relevance
“…Similar studies using Samanea waste leaves with broken papaya as the binder has also been carried out [19]. Another study found that briquettes using sawdust had the highest calorific value compared to coffee husk, khat waste, and dry grass [20].…”
Section: Introductionmentioning
confidence: 70%
See 1 more Smart Citation
“…Similar studies using Samanea waste leaves with broken papaya as the binder has also been carried out [19]. Another study found that briquettes using sawdust had the highest calorific value compared to coffee husk, khat waste, and dry grass [20].…”
Section: Introductionmentioning
confidence: 70%
“…After various experiments were carried out to determine the ratio of the mixture of coffee husk waste and its adhesive, it was found that after the pressing process, briquettes could still be formed without any adhesive. It highlights the strong potential of the coffee husk as a briquette when compared to various types of biomasses since previous studies have reported that a higher proportion of adhesive reduces the heating value of the briquettes [6,[19][20]. After finding the ideal adhesive composition, proximate analysis and ultimate analysis were carried out to determine the composition of the compounds and elements present in the coffee husk waste.…”
Section: Resultsmentioning
confidence: 99%
“…source. results from other reports reveal that briquettes made with sawdust residue exhibited a little lower moisture content compared to coffee husk, khat waste, and dry grass residues and the presence of high volatile matter in wood increases its affinity to burning which results from briquettes formation with a high percentage of binding agent influences the burning rate of briquets, the calorific value was seen high in sawdust compared to other agricultural residues [41].…”
Section: Introductionmentioning
confidence: 81%
“…These include investigations on a mixture of pine and peanut shells for briquette production [5], research on a blend of peanut shells and corn stover as briquette material [6], the creation of briquettes from corn cobs, corn stems, soybean shells, peanut shells, rice husks, and rice straw [7], the examination of the impact of shelled nut shell warming rates utilizing the TG-FTIR (Thermo gravimetry Fourier-transform infrared spectroscopy) method [8], and the utilization of palm oil shell waste as a raw material for briquette production [9]. Additionally, there are studies on designing briquette stoves using raw materials such as palm shells, durian skins, and coconut shells [10], producing briquettes from palm oil shell waste and acacia shell waste using the response surface method [11], creating briquettes from waste peanut shells using the pyrolysis method [12], forming briquettes from palm oil shells and mango shells [13], and manufacturing briquettes from sawdust, coffee skins, khat waste, and dry grass, with binders made from clay and paper waste [14]. Other research focuses on the utilization of rice husk waste as a material for briquette production [15], making briquettes from food waste using pyrolysis techniques [16], investigating heating methods for coal briquette samples [17], analyzing the burning characteristics of corn straw briquettes using thermogravimetry analysis [18], exploring the use of palm oil shells as a source for charcoal briquettes [19], and utilizing rice husks and palm shells as raw materials for charcoal briquettes with starch adhesive [20].…”
Section: Introductionmentioning
confidence: 99%